Mutation Testing for Evaluating PHP Web Applications - Saifan, Ahmad A; Ata, Mahmoud Bani (International journal of software innovation, 2019)
Web applications provide services to hundreds of billions of people over the world, so they should be tested, to insure their validity. In this article, we are investigating the ability of testing web application based on traditional mutation testing. To perform this test, we have defined 54 mutation operators, classified into six categories: SQL data retrieving, data manipulation; domain name and IP address look up; internet protocol and service information; HTTP; connection to server and to database. The test was applied to websites that are built using PHP programming for two reasons. The majority of websites nowadays are built using ASP.net or PHP and most of the testing efforts that have been applied on web applications were using the Java programming language. We have implemented a prototype tool called μWebPHP for automatically generating mutants for PHP web applications based on the identified mutation operators. We report preliminary results that show that mutation testing is feasible for web applications.